A Coordinated Strategic Reserve to Safeguard the European Energy Transition - Karsten Neuhoff; Jochen Diekmann; Friedrich Kunz; Sophia Rüster; Wolf-Peter Schill; Sebastian Schwenen (Utilities Policy, 2016)
In Germany and beyond, various capacity mechanisms are currently being discussed with a view to improving the security of electricity supply. One of these mechanisms is a strategic reserve that retains generation capacity for use in times of critical supply shortage. We argue that strategic reserves have specific advantages compared to other capacity mechanisms in the context of the European energy transition. To date, however, the debate on capacity mechanisms has largely been restricted to national contexts. Against this background, we discuss the feasibility and potential benefits of coordinated cross-border strategic reserves to safeguard electricity supply and aid the energy transition in Germany and neighboring countries at large. Setting aside strategic reserve capacity which is deployed only in the event of extreme supply shortages could improve the security of electricity supply without distorting the EU's internal electricity market. In addition, overall costs may decrease when reserve procurement and activation are coordinated among countries, particularly if combined with flow-based market coupling.
Keywords: 330; Capacity mechanisms; Energy transition; Strategic reserve